Caribbean Report 07-02-1997 - Gordon, Warren (anchor); Amory, Vance (interviewee); Gifford, Anthony (interviewee); Norton, Michael (interviewee); Fraser, Tony (correspondent) (The British Broadcasting Corporation, 1997)
Nevisian Premier Vance Amory has announced snap elections and expects early elections to give a boost to his efforts to secede from the federation with St. Kitts. Next, the environmental group Greenpeace is once again appealing to Caricom nations to take action to band nuclear waste shipment through the region. Next, following a controversial ruling by a judge presiding over a case of alleged rape, the Jamaican Bar Association is calling for the creation of a code of judicial conduct. Next, the President of Haiti Renee Preval has distributed tens of thousands of acres of land to poor farmers. it is being described as the fulfilment of a promise that is two centuries old. Next, through a local company, Cable and Wireless, the Internet is accessible to every child in Bermuda. However, the government, has had to set up some controls to ensure that the children do not access the wrong kind of information. Next, United States immigrations officials say that the number of illegal immigrants in the country has drastically increased. More than half are from Mexico, El Salvador, Haiti, Guatemala and Canada. Some entered illegally while others overstayed their visas. Finally, Trinidad and Tobago’s calypso reflects the state of the society and this year is no different. The finals of the Calypso Monarch competition has a number of songs on the race relations in the country.
1. Headlines (00:00-00:29)
2. The Premier of Nevis defends his decision to call a snap elections. Premier of Nevis, Vance Amory is interviewed (00:30:03:41)
3. The Environmental Group Greenpeace renews a call to Caricom nations to ban nuclear waste shipments through the region (03:42:04:39)
4. The Jamaican Bar Association is calling for the creation of a code of judicial conduct. Lord Jefford,QC is interviewed (04:40-10:34)
Keywords: Nevis Reformation Party.; Snap elections -- Nevis.; Secession -- Nevis.; Secession -- St Kitts.; Environmental Group Greenpeace.; Nuclear wate shipment -- Caribbean.; Jamaican Bar Association.; Rape -- Jamaica.; Judicial conduct -- Jamaica.; Land distribution -- Haiti.; Poor Farmers -- Haiti.; Internet -- Bermuda.; Cable and Wireless -- Bermuda.; Immigration -- United States.; Calypso -- Trinidad and Tobago.; International Monarch Competition -- Trinidad and Tobago.